The Phonological Acquisition of Children at Linguistic Period - Ummi Umara; Conny Conny; Tri Indah Rezeki; Rakhmat Wahyudin Sagala (Muhammadiyah University of Mataram, 2021)
In general, the development of a child's language is separated into two stages: the Pralinguistic and Linguistic periods. The goal of this research is to examine the phonological study of child language acquisition during the linguistic period, which covers vowel and consonant acquisition, as well as factors that influence phonology acquisition. This study looks at the following questions: 1) What factors influence a child's phonological acquisition during the language period? 2) How does a four-year-old learn voices and consonants? 3) What is the reason for the child's phonological acquisition? This study used a case study approach to qualitative research. The data was gathered by observation, documentation, and interviews from the utterances of a 4-year-old named TRS. Meanwhile, phonological analysis was used to examine the data. TRS has mastered vocal phonemes since she was two years old, according to the findings of this study. The consonant [r] and its vibrating sound have yet to develop and be mastered. The lack of a proper pronunciation of TRS is partly to blame for the formation of significant differences in the acquisition of TRS phonology. In other words, the TRS language's phonological acquisition has not yet achieved its peak.